Institutional support for postgraduate study in Malaysia / Gurnam Kaur Sidhu … [et al.] - Kaur Sidhu, Gurnam; Kaur, Sarjit; Lim, Peck Choo; Yuen Fook, Chan; Lai Fong, Lee; Jamian, Leele Susana (Penerbit UiTM (UiTM Press), 2015)
The twin forces of globalisation and internationalisation witnessed the global democratisation of higher education leading to the mushrooming of institutions of higher learning alongside with the rapid increase in student enrolments at all levels including postgraduate study. Despite the rapid developments in higher education, postgraduate study has been plagued with high attrition and low completion rates. Consequently, there is a need to look into delivery systems to ensure students are not short-changed and quality education and delivery systems are maintained at all times. This paper aims to investigate institutional support provided for postgraduate study in Malaysia. This descriptive study involved a total of 121 supervisors and 209 postgraduate students from two public universities in Malaysia. Data for the study were collected using questionnaires and semi-structured interviews. The findings revealed that students and supervisors were moderately satisfied with the information support provided by their respective institutions with regards to postgraduate study and courses. Nevertheless, students felt that institutional support was lacking in terms of facilities, professional development and opportunities for setting up learning communities. Supervisors too expressed the need for better postgraduate facilities, professional development and sought for more transparency in terms of grant and fellowship applications. Both groups also voiced concern regarding the knowledge, skills and attitude of administrators and clerical staff. These findings have implications for the need of quality delivery systems, especially institutional support for postgraduate study.